Grand Challenges of Interdisciplinarity: A View from the Humanities - Žic Fuchs, Milena (Array, 2010)
The notion of Grand Challenges is discussed from the point of view of Humanities research. Special attention is paid to implications for resetting research agendas, implications of the global dimension and issues pertaining to bridging the gap between disciplines and research domains. The balance between deep interdisciplinarity and monodisciplinarity is also discussed.